Comparison Of The Burning Of A Single Diesel Droplet With Volume And Surface Contamination Of Soot Particles - Abdul Rasid, Ahmad Fuad; Yang Zhang (Elsevier Ltd, 2021)
Following an examination on the effect of soot contamination on the surface of a diesel droplet to the combustion characteristics, an investigation on a uniform suspension of diesel soot particles within a diesel droplet was conducted experimentally for the first time. The aim is to determine the effect of uniformly suspended soot to the evaporation characteristics of a diesel droplet. Soot formed by the combustion of diesel was collected and suspended uniformly within a neat diesel. The particle loadings were varied from 0.1% to 0.5% by mass and ignited in a single isolated droplet, normal gravity and ambient condition. It is found that the burning rate of contaminated droplets is lower than the neat condition in all particle loading. A critical loading was identified to be at 0.2% which has shown a slight improvement of the burning rate despite having a reduced rate compared to its neat counterpart. It is found that within the critical loading, the particle briefly improves the thermal conductivity towards the core of the droplet which in turn slightly enhances the evaporation rate. Once the shear stress exerted by the external gas flow is subjected to the droplet, the internal circulation is induced and moves the particle towards the surface of the droplet. Agglomeration of particles on the surface of the droplet inhibit the liquid diffusion from the core to the surface of the droplet thus suppressing the evaporation rate. High particle loading would accelerate the agglomeration process whereas a low and critical particle loading briefly improves the evaporation in a reduced condition. These insights are of significance for determining the main cause of the detrimental effect from soot contamination in a liquid fuel; providing a base approach upon identifying the role of nanoparticles within the fuel droplet combustion study.